Electrolyte composite and method for producing the same, solid electrolyte membrane, solid battery, battery pack, and power-using device
Patent Information
- Application Number
- CN202510482534.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2026-10-23
AI Technical Summary
其中元素掺杂的主要问题是掺杂量和掺杂均匀性不可控,表面包覆的主要问题是包覆层不稳定以及活性颗粒与电解质之间的界面阻抗增大
[0040]本申请的第五方面提出了一种电池包。根据本申请的实施例,该电池包包括第一方面的电解质复合材料、第二方面所述方法制得的电解质复合材料、第三方面的固态电解质膜或者第四方面的固态电池。由此,有效提升了该电池包的电化学性能和安全性能。
Smart Images

Figure CN122968403A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of solid-state batteries, specifically relating to an electrolyte composite material and its preparation method, a solid electrolyte membrane, a solid-state battery, a battery pack, and an electrical device. Background Technology
[0002] Solid-state batteries, as the next generation of energy storage and power batteries, are attracting close attention from various fields. Among various solid electrolytes, sulfide solid electrolytes have become a current research hotspot due to their high ionic conductivity and moderate processability. However, the instability of sulfide electrolytes to air severely limits their industrial application. This is mainly because the PS bond formed between the hard acid P and the soft base S in sulfide electrolytes is unstable. P tends to combine with O in water to form a stronger PO bond, leading to changes in the electrolyte structure. In addition to damaging the electrolyte performance, sulfides produce H2S gas after absorbing water, which is highly toxic and can harm human health. Therefore, moisture in the air seriously affects the structural stability, ionic conductivity, and interfacial impedance of sulfide electrolytes, and can produce highly toxic gases through side reactions.
[0003] To reduce the impact of moisture on sulfide electrolytes, common physical methods include reducing the water content in the air, while chemical methods involve elemental doping and surface coating modification of the electrolyte. The main problems with elemental doping are the uncontrollable doping amount and uniformity, while the main problems with surface coating are the instability of the coating layer and the increased interfacial resistance between the active particles and the electrolyte. Summary of the Invention
[0004] This application aims to at least partially address one of the technical problems in related technologies. Therefore, the purpose of this application is to provide an electrolyte composite material and its preparation method, a solid electrolyte membrane, a solid-state battery, a battery pack, and an electrical device. The coating layer disposed on the electrolyte surface in this application can effectively prevent water intrusion into the electrolyte, suppress hydrolysis side reactions, and also possesses good ionic conductivity, effectively reducing the interfacial impedance between the electrolyte and active particles, thus ensuring that the electrochemical performance of the electrolyte is not affected. Furthermore, the coating layer exhibits excellent structural stability, further increasing the cycle life of the battery.
[0005] This application firstly discloses an electrolyte composite material. According to an embodiment of this application, the electrolyte composite material comprises:
[0006] Electrolytes; and
[0007] A coating layer disposed on at least a portion of the surface of the electrolyte, the coating layer comprising a block polymer comprising hydrophilic polymer segments and hydrophobic polymer segments, the hydrophilic polymer segments being located on at least a portion of the surface of the electrolyte, and the hydrophobic polymer segments being located on at least a portion of the surface of the hydrophilic polymer segments away from the electrolyte.
[0008] The electrolyte composite material of the above embodiments of this application has a coating layer formed on at least a portion of the electrolyte surface. The coating layer includes a block polymer, which comprises a hydrophilic polymer segment with high ionic conductivity and a hydrophobic polymer segment that inhibits water erosion of the electrolyte. Therefore, the coating layer formed on the electrolyte surface of this application can effectively block water intrusion into the electrolyte, suppress hydrolysis side reactions, and also has good ionic conductivity, effectively reducing the interfacial impedance between the electrolyte and active particles, thus ensuring that the electrochemical performance of the electrolyte is not affected. Furthermore, the coating layer has excellent structural stability, further increasing the cycle life of the battery.
[0009] In addition, the electrolyte composite material according to the above embodiments of this application may also have the following additional technical features:
[0010] In some embodiments of this application, the hydrophilic polymer segment includes at least one of polyether, polypolyamine, polypolyol, polypolyacid, polyamide, and polypolythiol.
[0011] In some embodiments of this application, the polyether comprises at least one of polyethylene glycol, polypropylene oxide, and polybutane; and / or, the polypolyamine comprises at least one of polydopamine, polyacrylamide, ammonium polyphosphate, and deacetylated chitosan; and / or, the polypolyol comprises at least one of polyvinyl alcohol, polyacrylamide, polybutenol, and polyhydroxycellulose; and / or, the polypolyacid comprises at least one of polyacrylic acid, sodium polyacrylate, and polybutenoic acid; and / or, the polyamide comprises at least one of polyacrylamide, propargylamide polymer, and sulfonated polyamide; and / or, the polypolythiol comprises at least one of mercaptopolyethylene glycol thiol and polyvinylthiol.
[0012] In some embodiments of this application, the degree of polymerization of the hydrophilic polymer segment is 200 to 2500.
[0013] In some embodiments of this application, the degree of polymerization of the polyethylene glycol is 400 to 2000.
[0014] In some embodiments of this application, the hydrophobic polymer segment includes at least one of polysiloxane, polyester, polyamine, saturated alkyl polymer and unsaturated hydrocarbon polymer.
[0015] In some embodiments of this application, the polysiloxane includes at least one of polydimethylsiloxane and its derivatives; and / or, the polyester includes at least one of polymethyl methacrylate, polyacrylate, polycarbonate diol, and polyester fiber; and / or, the polyamine includes at least one of polyimide, polyethyleneimine, and chitin; and / or, the saturated alkyl polymer includes at least one of polyethylene, polyvinyl chloride, and polypropylene; and / or, the unsaturated hydrocarbon polymer includes at least one of polyacetylenes and their derivatives.
[0016] In some embodiments of this application, the degree of polymerization of the hydrophobic polymer segment is 500 to 3000.
[0017] In some embodiments of this application, the degree of polymerization of the polydimethylsiloxane is 700 to 2000.
[0018] In some embodiments of this application, the block polymer has a cross-linked network structure, and the structural formula of the block polymer is:
[0019]
[0020]
[0021] Wherein, A is the hydrophilic polymer segment, Q is the hydrophobic polymer segment, CCR is the group formed by the double bond end-capping agent, n1 is a positive integer in the range of 100 to 2000, and n2 is a positive integer in the range of 100 to 2000.
[0022] In some embodiments of this application, the double bond end-capping agent includes an isocyanate end-capping agent, which includes at least one of isophorone diisocyanate and isocyanoethyl methacrylate.
[0023] In some embodiments of this application, the coating layer further includes metal oxides and / or lithium salts.
[0024] In some embodiments of this application, the mass ratio of the block polymer to the metal oxide is (4-16):1; and / or, the mass ratio of the hydrophilic polymer segment in the block polymer to the lithium salt is (2-8):1.
[0025] In some embodiments of this application, the metal oxide includes at least one of Fe2O3, ZnO, TiO2, Bi2O3, and SnO2; and / or, the lithium salt includes at least one of LiPF6, LiBF4, LiClO4, LiAsF6, LiTFSI, LiFSI, LiBOB, LiDFOB, and LiTFOP.
[0026] In some embodiments of this application, the particle size D50 of the electrolyte is 0.5 μm to 5 μm; and / or the thickness of the coating layer is 7 nm to 30 nm.
[0027] In some embodiments of this application, the electrolyte includes at least one of sulfide electrolytes, halide electrolytes, oxide electrolytes, and polymer electrolytes.
[0028] A second aspect of this application provides a method for preparing the electrolyte composite material of the above embodiments. According to an embodiment of this application, the method includes:
[0029] Electrolytes, block polymers, and organic solvents are mixed to obtain a suspension;
[0030] The suspension is subjected to solid-liquid separation and dried to obtain an electrolyte composite material.
[0031] The method for preparing electrolyte composite materials according to the above embodiments of this application involves forming a coating layer on at least a portion of the surface of the electrolyte. The coating layer comprises a block polymer, which includes a hydrophilic polymer segment with high ionic conductivity and a hydrophobic polymer segment that inhibits water erosion of the electrolyte. Therefore, the coating layer formed on the electrolyte surface by this method can effectively block water intrusion into the electrolyte, suppress hydrolysis side reactions, and also possesses good ionic conductivity, effectively reducing the interfacial impedance between the electrolyte and active particles, thus ensuring that the electrochemical performance of the electrolyte remains unaffected. Furthermore, the coating layer exhibits excellent structural stability, further increasing the cycle life of the battery.
[0032] In addition, the method for preparing electrolyte composite materials according to the above embodiments of this application may also have the following additional technical features:
[0033] In some embodiments of this application, the mass ratio of the electrolyte to the block polymer is 1:(0.01 to 0.05).
[0034] In some embodiments of this application, the electrolyte, the block polymer, the organic solvent, and the metal oxide and / or lithium salt are mixed to obtain a suspension.
[0035] In some embodiments of this application, the process further includes mixing the suspension, crosslinking agent, and initiator, and heating them before performing solid-liquid separation on the suspension.
[0036] In some embodiments of this application, the mass ratio of the block polymer, the crosslinking agent, and the initiator is 1:(0.01~0.03):(0.001~0.007); and / or, the heating temperature is 45℃~60℃, and the heating time is 20min~40min.
[0037] In some embodiments of this application, the crosslinking agent includes at least one of peroxide crosslinking agents, azo compound crosslinking agents, acrylate crosslinking agents, and epoxy resin crosslinking agents; and / or, the initiator includes at least one of azo initiators, peroxide initiators, and redox initiators.
[0038] A third aspect of this application discloses a solid electrolyte membrane. According to embodiments of this application, the solid electrolyte membrane comprises an electrolyte composite material from the first aspect or an electrolyte composite material prepared by the method described in the second aspect. Therefore, the solid electrolyte membrane can effectively block water intrusion into the electrolyte, suppress hydrolysis side reactions, and also possesses good ionic conductivity, effectively reducing the interfacial impedance between the electrolyte and active particles, thus ensuring that the electrochemical performance of the electrolyte remains unaffected.
[0039] A fourth aspect of this application discloses a solid-state battery. According to embodiments of this application, the solid-state battery includes an electrolyte composite material as described in the first aspect, an electrolyte composite material prepared by the method described in the second aspect, or a solid electrolyte membrane as described in the third aspect. This effectively improves the electrochemical performance and safety performance of the solid-state battery.
[0040] A fifth aspect of this application discloses a battery pack. According to embodiments of this application, the battery pack includes an electrolyte composite material (as described in the first aspect), an electrolyte composite material prepared by the method of the second aspect, a solid electrolyte membrane (as described in the third aspect), or a solid-state battery (as described in the fourth aspect). This effectively improves the electrochemical performance and safety performance of the battery pack.
[0041] A sixth aspect of this application discloses an electrical device. According to an embodiment of this application, the electrical device includes a solid-state battery as described in the fourth aspect or a battery pack as described in the fifth aspect. Therefore, the features and advantages described above for solid-state batteries are also applicable to this electrical device, and will not be repeated here.
[0042] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0043] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:
[0044] Figure 1 This is a schematic diagram of the structure of the electrolyte composite material according to an embodiment of this application;
[0045] Figure 2 This is a schematic diagram showing the chain segment changes of the coating layer during electrolyte deformation according to an embodiment of this application.
[0046] Figure label:
[0047] 1-Electrolyte, 2-Coating layer, 2-1-Hydrophilic polymer segment, 2-2-Hydrophobic polymer segment. Detailed Implementation
[0048] The embodiments of this application are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain this application, and should not be construed as limiting this application.
[0049] The first aspect of this application discloses an air-stable electrolyte composite material. According to embodiments of this application, refer to the appendix... Figure 1 The electrolyte composite material includes an electrolyte 1 and a coating layer 2. The coating layer 2 is disposed on at least a portion of the surface of the electrolyte 1. The coating layer 2 includes a block polymer, which includes a hydrophilic polymer segment 2-1 and a hydrophobic polymer segment 2-2. The hydrophilic polymer segment 2-1 is located on at least a portion of the surface of the electrolyte 1, and the hydrophobic polymer segment 2-2 is located on at least a portion of the surface of the hydrophilic polymer segment 2-1 away from the electrolyte 1.
[0050] The electrolyte composite material of the above embodiments of this application has a coating layer formed on at least a portion of the electrolyte surface. The coating layer includes a block polymer, which comprises a hydrophilic polymer segment with high ionic conductivity and a hydrophobic polymer segment that inhibits water erosion of the electrolyte. Therefore, the coating layer formed on the electrolyte surface of this application can effectively block water intrusion into the electrolyte, suppress hydrolysis side reactions, and also has good ionic conductivity, effectively reducing the interfacial impedance between the electrolyte and active particles, thus ensuring that the electrochemical performance of the electrolyte is not affected. Furthermore, the coating layer exhibits excellent structural stability.
[0051] Furthermore, the hydrophilic polymer segments are tightly anchored to the surface of the electrolyte (especially the sulfide electrolyte) by van der Waals forces, providing good ionic conductivity while serving as the first protective layer, which can effectively reduce the interfacial impedance between the electrolyte and the active particles.
[0052] Furthermore, the hydrophobic polymer segments tend to cluster on the surface of the hydrophilic polymer segments, acting as a second protective layer. This effectively blocks water intrusion into the electrolyte and suppresses hydrolysis side reactions, resulting in superior air stability of the electrolyte composite material. Simultaneously, the coating layer on the electrolyte surface effectively inhibits direct contact between the electrolyte and active components such as the lithium metal anode, thereby significantly improving the chemical stability of the electrolyte.
[0053] Furthermore, the hydrophobic polymer segments in the block polymer exhibit a reversible cluster structure on the electrolyte surface, as shown in the attached figure. Figure 2When the electrolyte expands, the block polymer is subjected to expansion force, and its outermost hydrophobic cluster structure can stretch to release stress; when the electrolyte contracts, the expansion force on the polymer disappears, and the hydrophobic segments contract to restore the cluster structure. This process is a reversible deformation, which further enhances the structural stability of the coating layer.
[0054] Furthermore, the block polymers in the coating layer can form a stable three-dimensional network structure with reversible deformation capabilities through chemical cross-linking, which greatly improves the structural stability of the coating layer.
[0055] According to some specific embodiments of this application, the aforementioned hydrophilic polymer segments include at least one of polyethers (preferably short-chain polyethers), polypolyamines, polypolyols, polypolyacids, polyamides, and polypolythiols. All of these types of hydrophilic polymer segments possess high conductivity, and all of these hydrophilic polymers can be tightly anchored to the surface of the electrolyte (especially sulfide electrolytes) through van der Waals forces, providing good ionic conductivity while serving as a first protective layer. Short-chain polyethers are preferred, i.e., short-chain ether polymers. The advantages of ether polymers are: first, ether polymers do not contain active functional groups and do not exhibit significant side reactions with the electrolyte (especially sulfide electrolytes), thus eliminating the need for interface modification; second, ether polymers have good lithium affinity and can complex with lithium salts to form stable composite structures, improving the ionic conductivity of the polymer; furthermore, after lithium ions coordinate with oxygen on the polymer chain segments, the activity of oxygen decreases, which can also improve the contact stability between the polymer and the electrolyte.
[0056] In the embodiments of this application, the specific types of the aforementioned short-chain polyethers are not particularly limited. As some preferred embodiments, the aforementioned short-chain polyethers include at least one selected from polyethylene glycol (PEG), polypropylene oxide, and polybutane. The specific types of the aforementioned polypolyamines are also not particularly limited. As some preferred embodiments, polypolyamines include at least one selected from polydopamine, polyacrylamide, ammonium polyphosphate, and deacetylated chitosan. The specific types of the aforementioned polypolyols are also not particularly limited. As some preferred embodiments, polypolyols include at least one selected from polyvinyl alcohol, polyacrylamide, polybutenol, and polyhydroxycellulose. The specific types of the aforementioned polypolyacids are also not particularly limited. As some preferred embodiments, polypolyacids include at least one selected from polyacrylic acid, sodium polyacrylate, and polybutenoic acid. The specific types of the aforementioned polyamides are also not particularly limited. As some preferred embodiments, polyamides include at least one selected from polyacrylamide, propargyl amide polymer, and sulfonated polyamide. The specific types of the aforementioned polypolythiols are also not particularly limited. As some preferred embodiments, polypolythiols include at least one selected from mercaptopolyethylene glycol thiols and polyvinylthiols.
[0057] According to some specific embodiments of this application, the degree of polymerization of the hydrophilic polymer segment is 200 to 2500, for example, 200, 400, 800, 1000, 1200, 1500, 1800, 2000, 2500, etc. The inventors have found that by limiting the degree of polymerization of the hydrophilic polymer segment to the above range, the ionic conductivity of the coating layer can be effectively ensured, while avoiding the problem of uneven coating caused by excessively high molecular polymerization of the hydrophilic polymer segment leading to increased viscosity of the block polymer and easy self-aggregation to form stable micelles.
[0058] According to some specific embodiments of this application, the degree of polymerization of the aforementioned polyethylene glycol (PEG) is 400–2000, for example, 400, 800, 1000, 1200, 1500, 1800, 2000, etc. The inventors have found that if the degree of polymerization of the polyethylene glycol is too low, it will affect the ionic conductivity of the coating layer; if the degree of polymerization of the polyethylene glycol is too high, it will lead to an increase in the viscosity of the block polymer and a tendency to self-aggregate to form stable micelles, resulting in uneven coating.
[0059] According to some specific embodiments of this application, the hydrophobic polymer segment includes at least one of polysiloxane, polyester, polyamine, saturated alkyl polymer, and unsaturated hydrocarbon polymer. These types of hydrophobic polymers tend to aggregate in clusters on the surface of the hydrophilic polymer segment, serving as a second protective layer to effectively block water intrusion into the electrolyte and suppress hydrolysis side reactions. Polysiloxane is preferred.
[0060] In the embodiments of this application, the specific type of polysiloxane is not particularly limited. As some preferred embodiments, the polysiloxane includes at least one of polydimethylsiloxane (PDMS) and its derivatives. Polydimethylsiloxane (PDMS) is preferred, as PDMS has advantages in terms of good temperature stability, chemical structural stability, and corrosion resistance.
[0061] In the embodiments of this application, the specific type of polyester is not particularly limited. As some preferred embodiments, the polyester includes at least one of polymethyl methacrylate, polyacrylate, polycarbonate diol, and polyester fiber. In the embodiments of this application, the specific type of polyamine is not particularly limited. As some preferred embodiments, the polyamine includes at least one of polyimide, polyethyleneimine, and chitin. The specific type of the saturated alkyl polymer is not particularly limited. As some preferred embodiments, the saturated alkyl polymer includes at least one of polyethylene, polyvinyl chloride, and polypropylene. The specific type of the unsaturated hydrocarbon polymer is not particularly limited. As some preferred embodiments, the unsaturated hydrocarbon polymer includes at least one of polyacetylenes and their derivatives.
[0062] According to some specific embodiments of this application, the degree of polymerization of the hydrophobic polymer segment is 500 to 3000, for example, it can be 500, 700, 800, 1000, 1200, 1500, 1800, 2000, 2500, 3000, etc. The inventors have found that by limiting the degree of polymerization of the hydrophobic polymer segment to the above range, the coating layer can effectively ensure its ability to block water intrusion into the electrolyte, while avoiding the problem of uneven coating caused by excessively high molecular polymerization of the hydrophobic polymer segment leading to increased viscosity of the block polymer and easy self-aggregation to form stable micelles.
[0063] According to some specific embodiments of this application, the degree of polymerization of polydimethylsiloxane is 700-2000, for example, it can be 700, 800, 1000, 1200, 1500, 1800, 2000, etc. The inventors have found that if the degree of polymerization of polydimethylsiloxane is too low, it will affect the coating layer's ability to prevent water from entering the electrolyte; if the degree of polymerization of polydimethylsiloxane is too high, it will lead to an increase in the viscosity of the block polymer and a tendency to self-aggregate to form stable micelles, resulting in uneven coating.
[0064] According to further embodiments of this application, the block polymer has a cross-linked network structure, and the structural formula of the block polymer is as follows:
[0065]
[0066] In this designation, A represents the hydrophilic polymer segment, Q represents the hydrophobic polymer segment, CCR represents the double bond end-capping group, n1 is a positive integer between 100 and 2000, and n2 is a positive integer between 100 and 2000. Therefore, the block polymer with a three-dimensional network structure exhibits greater structural stability and will not slip or collapse due to external forces during electrolyte storage and use, further enhancing the structural stability of the coating layer.
[0067] According to further embodiments of this application, the double bond end-capping agent includes isocyanate end-capping agents, which can effectively ensure that the block polymer is end-capped with double bonds. Preferably, the isocyanate end-capping agent includes at least one of isophorone diisocyanate (IPDI) and isocyanate ethyl methacrylate (IEM), which has the advantages of low reactivity, structural stability, and good light and corrosion resistance under initiator-free conditions.
[0068] According to further embodiments of this application, the coating layer further includes a metal oxide and / or a lithium salt, wherein lithium ions in the lithium salt can form an ionic complex structure with hydrophilic groups (e.g., oxygen atoms) in the hydrophilic segment, thereby effectively improving the ionic conductivity of the block polymer. Metal atoms and oxygen atoms in the metal oxide can form a metal coordination structure, effectively absorbing H2S generated by side reactions. The lithium salt and metal oxide can effectively improve the electrochemical performance and safety performance of the battery.
[0069] According to some embodiments of this application, the mass ratio of block polymer to metal oxide is (4-16):1, for example, it can be 4:1, 6:1, 8:1, 10:1, 12:1, 16:1, etc., thereby further ensuring the effective absorption of H2S generated by side reactions.
[0070] According to some embodiments of this application, the mass ratio of the hydrophilic polymer segment to the lithium salt in the block polymer is (2-8):1, for example, it can be 2:1, 4:1, 6:1, 8:1, etc., thereby further ensuring that the lithium ions in the lithium salt can form an ionic complex structure with the oxygen atoms in the hydrophilic segment, thereby effectively improving the ionic conductivity of the block polymer.
[0071] In the embodiments of this application, the specific types of the metal oxides are not particularly limited. As some preferred embodiments, the metal oxides include at least one of Fe2O3, ZnO, TiO2, Bi2O3, and SnO2.
[0072] In the embodiments of this application, the specific type of lithium salt is not particularly limited. As some preferred embodiments, the lithium salt includes at least one of LiPF6, LiBF4, LiClO4, LiAsF6, LiTFSI, LiFSI, LiBOB, LiDFOB, and LiTFOP.
[0073] According to some embodiments of this application, the particle size D50 of the electrolyte is 0.5 μm to 5 μm, for example, it can be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm.
[0074] It should be noted that particle size D50 represents the particle size corresponding to a cumulative particle size distribution percentage of 50% for the sample. In the embodiments of this application, the particle size distribution can be tested using methods such as laser particle size analysis (utilizing the principle of laser diffraction, where scattering occurs when a laser beam irradiates particles, and the particle size distribution is calculated by measuring the intensity and angle of the scattered light), sieving (grading particles through a series of sieves with different apertures, and calculating the particle size distribution based on the sieve apertures and the amount of particles remaining on the sieves), and sedimentation (based on Stokes' law, the settling velocity of particles in a liquid is related to their particle size, density, and the viscosity of the liquid; the particle size distribution is calculated by measuring the settling velocity of the particles in the liquid).
[0075] According to some embodiments of this application, the thickness of the coating layer is 7nm to 30nm, for example, it can be 7nm, 10nm, 12nm, 15nm, 20nm, 25nm, 30nm, etc. By limiting the thickness of the coating layer within the above range, it can be further ensured that the coating layer effectively blocks water from entering the electrolyte, inhibits hydrolysis side reactions, and also has good ionic conductivity.
[0076] The hydrophobic effect of the electrolyte composite material of this application can be controlled by adjusting the molecular weight of the hydrophilic and hydrophobic segments and the thickness of the coating layer. The larger the molecular weight of the hydrophobic segment and the thicker the coating layer, the better the hydrophobic effect of the electrolyte composite material.
[0077] The technical solution of this application is applicable not only to sulfide electrolytes, but also to at least one of halide electrolytes, oxide electrolytes and polymer electrolytes, and is particularly applicable to sulfide electrolytes.
[0078] In the embodiments of this application, the specific type of the sulfide electrolyte is not particularly limited. As some preferred embodiments, the sulfide electrolyte includes Li6PS5Br and Li7P3S. 11 Li 10 GeP2S 12 Li6PS5Cl, Li 6+x P 1- x Ge x S5I, Li6PS5Cl y Br 1-y , Li5PS4(X1)2, zLi2S·(100-z)P2S5, Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 Li 10 JP2S 12, at least one of Li5PS4(X2)2, wherein x is in the range of 0 to 1, y is in the range of 0 to 1, z is in the range of 60 to 80, X1 is Cl, Br or I, J is Si, Ge or Sn, and X2 is Cl, Br or I.
[0079] In the embodiments of the present application, the specific type of the above halide electrolyte is not particularly limited. As some preferred embodiments, the halide electrolyte includes Li3Er(X3)6, Li3LaI6, Li3LuCl6, Li3InBr 6-a Cl a , Li3InBr3Cl3, Li3InBr6, Li3InCl6, LiInBr4, CsSnCl3, Li b ScCl 3+b , Li3Sc(X4)6, Li 3-c Er 1-c Zr c Cl6, Li 3-d Y 1-d Zr d Cl6, Li3Y(X5)6, Li3Y 1-e In e Cl6, wherein X3 is Cl, Br or I, X4 is Cl, Br or I, X5 is Cl, Br or I, a is in the range of 0 < a ≤ 4, b is in the range of 1 to 3, c is in the range of 0 < c ≤ 0.6, d is in the range of 0 < d ≤ 0.6, and e is in the range of 0 ≤ e < 1.
[0080] In the embodiments of the present application, the specific type of the above oxide electrolyte is not particularly limited. As some preferred embodiments, the oxide electrolyte includes at least one of AB2(MO4)3 (A=alkali metal, B is Ge, Zr, Ti or V, M is Mo or P, etc.), Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 0.5 La 0.5 TiO3, Li5La3M2O 12 (M is Ta, Nb or Zr), L i M 1-y A y S4 (M is Si or Ge; A is P, Al, Zn, Ga or Sb, 0 ≤ y ≤ 1), and LiAlO2.
[0081] In the embodiments of this application, the specific type of polymer electrolyte is not particularly limited. As some preferred embodiments, the polymer electrolyte includes at least one of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), polypropylene carbonate (PPC), polyethylene oxide (PEO), and ethylene oxide-propylene oxide copolymer (PEO-PO).
[0082] A second aspect of this application provides a method for preparing the electrolyte composite material of the above embodiments. According to an embodiment of this application, the method includes:
[0083] S100: Electrolyte, block polymer and organic solvent are mixed to obtain a suspension;
[0084] In this step, the electrolyte is first dissolved in an organic solvent and dispersed evenly. Then, the block polymer is added and stirring continues to obtain a suspension. Based on the adsorption property of the electrolyte (the property of the electrolyte adsorbing the polymer) and the amphiphilicity (i.e., hydrophilicity and hydrophobicity) of the block polymer, the block polymer is uniformly coated on the surface of the electrolyte with the hydrophobic segments of the block polymer facing the organic solvent. Thus, the block polymer forms a coating layer on the surface of the electrolyte.
[0085] According to some specific embodiments of this application, the mass ratio of electrolyte to block polymer is 1:(0.01 to 0.05), for example, it can be 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, etc. Therefore, by limiting the mass ratio of electrolyte to block polymer to the above range, it can be further ensured that the coating layer formed by block polymer on the electrolyte surface effectively blocks water from entering the electrolyte, suppresses hydrolysis side reactions, and also has good ionic conductivity.
[0086] According to further specific embodiments of this application, an electrolyte, a block polymer, an organic solvent, and a metal oxide and / or lithium salt are mixed to obtain a suspension, wherein the coating layer formed on the surface of the electrolyte further includes the metal oxide and / or lithium salt. The lithium ions in the lithium salt can form an ionic complex structure with the oxygen atoms in the hydrophilic segments of the block polymer, thereby effectively improving the ionic conductivity of the block polymer. The metal atoms and oxygen atoms in the metal oxide can form a metal coordination structure, effectively absorbing H2S generated by side reactions. The lithium salt and metal oxide can effectively improve the electrochemical performance and safety performance of the battery.
[0087] The preparation method of the above-mentioned block polymer is not particularly limited. As a specific embodiment, the preparation method of the above-mentioned block polymer includes:
[0088] The first step involves an organic alkali metal initiator (such as n-butyllithium n-BuLi) initiating the ring-opening polymerization of hexamethylcyclotrisiloxane in tetrahydrofuran (THF) to form PDMS. Then, active linkers such as trimethyltrivinylcyclotrisiloxane are added, and another hydrophilic monomer (such as ethylene oxide) is added to the end of the polymer through a specific chemical reaction (such as a bridging reaction) to form a block polymer with hydroxyl end groups.
[0089] In the second step, the block polymer generated in the first step is washed clean with ethanol, then dissolved in organic solvents such as dichloromethane and THF. Isocyanate molecules are added as end-capping agents, and dibutyltin dilaurate (DBTDL) is used as a catalyst to obtain a block polymer with double bonds at the ends. The double bonds introduced in this step provide crosslinking sites for the subsequent formation of the three-dimensional network.
[0090] S200: The suspension is subjected to solid-liquid separation and drying to obtain an electrolyte composite material.
[0091] In this step, a centrifuge can be used to separate the solid and liquid components of the suspension. After drying, an air-stable electrolyte composite material is obtained.
[0092] According to some specific embodiments of this application, before solid-liquid separation of the suspension, the process further includes mixing the suspension, crosslinking agent, and initiator, and heating. The crosslinking agent can effectively promote chemical crosslinking reactions between block polymers, forming a stable three-dimensional network structure with reversible deformation capabilities, thereby further improving the structural stability of the coating layer. The role of the initiator is to initiate the chemical crosslinking reaction between the block polymers promoted by the crosslinking agent.
[0093] According to some specific embodiments of this application, the mass ratio of block polymer, crosslinking agent and initiator is 1:(0.01-0.03):(0.001-0.007), thereby further ensuring that chemical crosslinking reaction occurs between the block polymers to form a stable three-dimensional network structure with reversible deformation capability.
[0094] According to some specific embodiments of this application, the heating temperature is 45°C to 60°C (e.g., 45°C, 50°C, 55°C, 60°C, etc.), and the heating time is 20 min to 40 min (e.g., 20 min, 25 min, 30 min, 35 min, 40 min, etc.). This further ensures that chemical cross-linking reactions occur between the block polymers, forming a stable three-dimensional network structure with reversible deformation capabilities.
[0095] In the embodiments of this application, the specific type of crosslinking agent is not particularly limited. As some preferred embodiments, the crosslinking agent includes at least one of peroxide crosslinking agents, azo compound crosslinking agents, acrylate crosslinking agents, and epoxy resin crosslinking agents. Acrylate crosslinking agents and epoxy resin crosslinking agents, such as ethylene glycol dimethacrylate (EGDMA), are more preferred because these crosslinking agents are non-toxic, inexpensive, have low steric hindrance, and most importantly, their structure is similar to that of the hydrophilic segment, resulting in no significant side reactions with the sulfide electrolyte.
[0096] In the embodiments of this application, the specific type of initiator is not particularly limited. As some preferred embodiments, the initiator includes at least one of azo initiators, peroxide initiators, and redox initiators.
[0097] In the embodiments of this application, the specific types of organic solvents are not particularly limited. As some preferred embodiments, the organic solvents are benzene-based solvents, such as toluene and xylene.
[0098] The method for preparing electrolyte composite materials according to the above embodiments of this application involves forming a coating layer on at least a portion of the surface of the electrolyte. The coating layer comprises a block polymer, which includes a hydrophilic polymer segment with high ionic conductivity and a hydrophobic polymer segment that inhibits water erosion of the electrolyte. Therefore, the coating layer formed on the electrolyte surface by this method can effectively block water intrusion into the electrolyte, suppress hydrolysis side reactions, and also possesses good ionic conductivity, effectively reducing the interfacial impedance between the electrolyte and active particles, thus ensuring that the electrochemical performance of the electrolyte remains unaffected. Furthermore, the coating layer exhibits excellent structural stability, further increasing the cycle life of the battery.
[0099] Furthermore, the hydrophilic polymer segments are tightly anchored to the surface of the electrolyte (especially the sulfide electrolyte) by van der Waals forces, providing good ionic conductivity while serving as the first protective layer, which can effectively reduce the interfacial impedance between the electrolyte and the active particles.
[0100] Furthermore, the hydrophobic polymer segments tend to cluster on the surface of the hydrophilic polymer segments, acting as a second protective layer. This effectively blocks moisture from penetrating the electrolyte and suppresses hydrolysis side reactions, resulting in superior air stability of the electrolyte composite material. Simultaneously, the coating layer formed on the electrolyte surface effectively inhibits direct contact between the electrolyte and active components such as the lithium metal anode, thereby significantly improving the electrolyte's chemical stability.
[0101] Furthermore, the hydrophobic polymer segments in the block polymer exhibit a reversible cluster structure on the electrolyte surface. When the electrolyte expands, the block polymer is subjected to expansion force, and its outermost hydrophobic cluster structure can expand to release stress. When the electrolyte contracts, the expansion force on the polymer disappears, and the hydrophobic segments contract to restore the cluster structure. This process is a reversible deformation, further enhancing the structural stability of the coating layer.
[0102] A third aspect of this application discloses a solid electrolyte membrane. According to embodiments of this application, the solid electrolyte membrane comprises an electrolyte composite material from the first aspect or an electrolyte composite material prepared by the method described in the second aspect. Therefore, the solid electrolyte membrane can effectively block water intrusion into the electrolyte, suppress hydrolysis side reactions, and also possesses good ionic conductivity, effectively reducing the interfacial impedance between the electrolyte and active particles, thus ensuring that the electrochemical performance of the electrolyte remains unaffected.
[0103] A fourth aspect of this application discloses a solid-state battery. According to embodiments of this application, the solid-state battery includes an electrolyte composite material as described in the first aspect, an electrolyte composite material prepared by the method described in the second aspect, or a solid electrolyte membrane as described in the third aspect. This effectively improves the electrochemical performance and safety performance of the solid-state battery.
[0104] A fifth aspect of this application discloses a battery pack. According to embodiments of this application, the battery pack includes an electrolyte composite material (as described in the first aspect), an electrolyte composite material prepared by the method of the second aspect, a solid electrolyte membrane (as described in the third aspect), or a solid-state battery (as described in the fourth aspect). This effectively improves the electrochemical performance and safety performance of the battery pack.
[0105] A sixth aspect of this application discloses an electrical device. According to an embodiment of this application, the electrical device includes a solid-state battery as described in the fourth aspect or a battery pack as described in the fifth aspect. Therefore, the features and advantages described above for solid-state batteries are also applicable to this electrical device, and will not be repeated here.
[0106] Solid-state battery cells, solid-state battery modules, and solid-state battery packs can be used as power sources for electrical devices or as energy storage units for electrical devices. Electrical devices can include, but are not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0107] As an electrical device, solid-state battery cells, solid-state battery modules, or solid-state battery packs can be selected according to their usage requirements.
[0108] As one example, the electrical device can be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the electrical device for solid-state batteries, solid-state battery packs or solid-state battery modules can be used.
[0109] Another example of the device could be a mobile phone, tablet computer, laptop computer, etc. Such devices typically require a thin and light design and can use solid-state battery cells as a power source.
[0110] It should be noted that the features and advantages described above for solid-state batteries also apply to this electrical device, and will not be repeated here.
[0111] The embodiments of this application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. In addition, unless otherwise specified, all reagents used in the following embodiments are commercially available or can be synthesized according to the methods described herein or known methods. For reaction conditions not listed, they are also readily available to those skilled in the art.
[0112] Example 1
[0113] This embodiment provides a sulfide electrolyte composite material, the preparation method of which includes:
[0114] (1) Preparation of block polymers, including the following steps:
[0115] The first step involves using n-butyllithium (n-BuLi) to initiate the ring-opening polymerization of hexamethylcyclotrisiloxane in tetrahydrofuran (THF) to form PDMS. Then, trimethyltrivinylcyclotrisiloxane is added, and another hydrophilic monomer, polyethylene glycol (PEG), is added to the end of the polymer through a bridging reaction to form a block polymer with hydroxyl end groups.
[0116] In the second step, the block polymer generated in the first step was washed with ethanol, dissolved in dichloromethane, and then an isocyanate molecule IEM was added as a capping agent and dibutyltin dilaurate (DBTDL) as a catalyst to obtain a block polymer with double bonds at the ends, the structural formula of which is as follows:
[0117]
[0118] Where X is
[0119]
[0120] That is, the degree of polymerization of the hydrophobic polymer segment PDMS is 1000, and the degree of polymerization of the hydrophilic polymer segment PEG is 700.
[0121] (2) Dissolve the sulfide electrolyte Li6PS5Cl with a particle size D50 of 3μm in the organic solvent toluene, disperse it evenly, and then add the above block polymer and continue stirring.
[0122] (3) Add crosslinking agent (EGDMA) and azo initiator (AIBN), disperse evenly, heat to 60℃, and maintain for 25 min to allow the block polymer to form a stable crosslinked network structure, thus obtaining a suspension. The mass ratio of block polymer, crosslinking agent (EGDMA), and azo initiator is 1:0.02:0.004.
[0123] (4) Centrifuge the suspension three times and bake it to obtain an air-stable sulfide electrolyte composite material.
[0124] Example 2
[0125] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0126] (1) The degree of polymerization of the hydrophobic polymer segment PDMS of the block polymer is controlled to be 700.
[0127] Example 3
[0128] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0129] (1) The degree of polymerization of the hydrophobic polymer segment PDMS of the block polymer is controlled to be 1500.
[0130] Example 4
[0131] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0132] (1) The degree of polymerization of the hydrophobic polymer segment PDMS of the block polymer is controlled to be 2000.
[0133] Example 5
[0134] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0135] (1) The degree of polymerization of the hydrophobic polymer segment PDMS of the block polymer is controlled to be 600.
[0136] Example 6
[0137] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0138] (1) The degree of polymerization of the hydrophobic polymer segment PDMS of the block polymer is controlled to be 2200.
[0139] Example 7
[0140] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0141] (1) The degree of polymerization of the hydrophilic polymer segment PEG is 400.
[0142] Example 8
[0143] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0144] (1) The degree of polymerization of the hydrophilic polymer segment PEG is 1000.
[0145] Example 9
[0146] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0147] (1) The degree of polymerization of the hydrophilic polymer segment PEG is 2000.
[0148] Example 10
[0149] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0150] (1) The degree of polymerization of the hydrophilic polymer segment PEG is 300.
[0151] Example 11
[0152] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0153] (1) The degree of polymerization of the hydrophilic polymer segment PEG is 2200.
[0154] Example 12
[0155] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0156] (1) Replace the hydrophobic polymer segment PDMS in Example 1 with polycarbonate diol.
[0157] Example 13
[0158] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0159] (1) Replace the hydrophobic polymer segment PDMS in Example 1 with polyimide.
[0160] Example 14
[0161] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0162] (1) Replace the hydrophilic polymer segment PEG in Example 1 with polyacrylamide.
[0163] Example 15
[0164] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0165] (1) Replace the hydrophilic polymer segment PEG in Example 1 with polyacrylol.
[0166] Example 16
[0167] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0168] (2) Replace the sulfide electrolyte Li6PS5Cl with a particle size D50 of 3 μm in Example 1 with the halide electrolyte Li3LaI6 with a particle size D50 of 1 μm.
[0169] Example 17
[0170] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0171] (2) Replace the sulfide electrolyte Li6PS5Cl with a particle size D50 of 3 μm in Example 1 with the halide electrolyte Li3InCl6 with a particle size D50 of 3 μm.
[0172] Example 18
[0173] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0174] (2) The sulfide electrolyte Li6PS5Cl with a particle size D50 of 3 μm was dissolved in the organic solvent toluene, and after being dispersed evenly, the above block polymer and lithium salt LiTFSI were added and the mixture was stirred. The mass ratio of the hydrophilic polymer segment PEG and the lithium salt LiTFSI in the block polymer was 2:1.
[0175] Example 19
[0176] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0177] (2) The sulfide electrolyte Li6PS5Cl with a particle size D50 of 3 μm was dissolved in the organic solvent toluene, and after being dispersed evenly, the above block polymer and lithium salt LiTFSI were added and the mixture was stirred. The mass ratio of the hydrophilic polymer segment PEG and the lithium salt LiTFSI in the block polymer was 5:1.
[0178] Example 20
[0179] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0180] (2) The sulfide electrolyte Li6PS5Cl with a particle size D50 of 3 μm was dissolved in the organic solvent toluene, and after being dispersed evenly, the above block polymer and lithium salt LiTFSI were added and the mixture was stirred. The mass ratio of the hydrophilic polymer segment PEG and the lithium salt LiTFSI in the block polymer was 8:1.
[0181] Example 21
[0182] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0183] (2) The sulfide electrolyte Li6PS5Cl with a particle size D50 of 3 μm was dissolved in the organic solvent toluene, and after being dispersed evenly, the above block polymer and metal oxide TiO2 were added and the mixture was stirred. The mass ratio of the block polymer to the metal oxide TiO2 was 4:1.
[0184] Example 22
[0185] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0186] (2) The sulfide electrolyte Li6PS5Cl with a particle size D50 of 3 μm was dissolved in the organic solvent toluene, and after being dispersed evenly, the above block polymer and metal oxide TiO2 were added and the mixture was stirred. The mass ratio of the block polymer to the metal oxide TiO2 was 10:1.
[0187] Example 23
[0188] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0189] (2) The sulfide electrolyte Li6PS5Cl with a particle size D50 of 3 μm was dissolved in the organic solvent toluene, and after being dispersed evenly, the above block polymer and metal oxide TiO2 were added and the mixture was stirred. The mass ratio of the block polymer to the metal oxide TiO2 was 16:1.
[0190] Example 24
[0191] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0192] (2) The sulfide electrolyte Li6PS5Cl with a particle size D50 of 3 μm was dissolved in the organic solvent toluene, and after being dispersed evenly, the above block polymer, lithium salt LiTFSI and metal oxide TiO2 were added and the mixture was stirred. The mass ratio of block polymer to metal oxide TiO2 was 10:1, and the mass ratio of hydrophilic polymer segment PEG to lithium salt LiTFSI in the block polymer was 5:1.
[0193] Example 25
[0194] The preparation method in this embodiment is basically the same as that in Example 1, except that:
[0195] (1) The second step is not included, i.e., the block polymer is not designed with double bond end capping. The molecular formula of the block polymer is the structure of X in Example 1.
[0196] Comparative Example 1
[0197] This comparative example uses a conventional sulfide electrolyte Li6PS5Cl without a coating layer, with a particle size D50 of 3 μm.
[0198] Comparative Example 2
[0199] The preparation method of this comparative example is basically the same as that of Example 1, except that:
[0200] In the first step of the block polymer synthesis, the hydrophilic monomer PEG is not added. The other steps are the same as in Example 1.
[0201] Comparative Example 3
[0202] The preparation method of this comparative example is basically the same as that of Example 1, except that:
[0203] The preparation of block polymers includes the following steps:
[0204] The first step involves dissolving the hydrophilic monomer polyethylene glycol (PEG) in anhydrous dichloromethane, adding triethylamine as a catalyst, and slowly adding acryloyl chloride dropwise under ice bath conditions, reacting at room temperature for 16 hours.
[0205] The second step involves filtration and precipitation with diethyl ether to purify the product, followed by drying to obtain PEO with double bonds at the terminal groups.
[0206] Reaction route and structural formula: PEG-OH + acryloyl chloride → PEG-O-CO-CH2-CH2=CH2, with a degree of polymerization of 2400.
[0207] The thickness of the coating layer on the surface of the electrolyte composite material in Examples 1-25 and Comparative Examples 2-3 was tested, and the results are shown in Table 1.
[0208] Testing the thickness of the coating layer on the electrolyte surface:
[0209] The morphology and thickness of the coating layer on the electrolyte surface were characterized using cryo-transmission electron microscopy (TEM). The specific steps are as follows: the electrolyte particles to be tested were dispersed, and an appropriate number of particles were frozen in liquid nitrogen for testing; the sample was uniformly dispersed on a carbon fiber mesh for observation in the electron microscope; the sample was loaded and imaged, and parameters such as electron beam intensity and focal length were adjusted to obtain high-resolution images; the coating layer thickness was measured using image analysis tools.
[0210] Ionic conductivity test: Weigh appropriate amounts of electrolyte composite materials from Examples 1-25 and Comparative Examples 1-3 into a sulfide mold, pressurize and form a mold battery, and perform room temperature electrochemical EIS test.
[0211] Battery performance testing: The electrolyte composite materials of Examples 1-25 and Comparative Examples 1-3, along with the binder PVDF, were dissolved in xylene solvent at a mass ratio of 99:1 to form an electrolyte slurry. This slurry was then sprayed onto the receiving membrane and dried to obtain a solid electrolyte membrane with a thickness of 40 μm. Additionally, the positive electrode sheet includes a 16 μm thick carbon-coated aluminum foil current collector and a positive electrode active material layer disposed on the surface of the current collector. The positive electrode active material layer comprises 80 wt% ternary material LiNi. 0.8 Co 0.1 Mn 0.1 The electrolyte composite material, prepared above, consists of O2, 16 wt% of the above-prepared electrolyte composite material, 3 wt% of PVDF binder, and 1 wt% of carbon black conductive agent. The negative electrode comprises a 6 μm thick copper foil current collector and a negative electrode active material layer disposed on the surface of the current collector. The negative electrode active material layer comprises 96 wt% pure silicon, 3.5 wt% PVDF binder, and 0.5 wt% carbon black conductive agent. The positive electrode, negative electrode, and electrolyte are then assembled into a pouch cell for routine electrochemical performance testing. The test voltage is 2.2V-4.2V, and the charge / discharge rate is 0.5C. The test results are shown in Table 1.
[0212] Table 1
[0213]
[0214]
[0215] As shown in Table 1, compared with Comparative Example 1, the number of cycles corresponding to the 0.5C / 80% capacity retention rate in Examples 1-25 was significantly improved; compared with Comparative Example 2, both the room temperature ionic conductivity and the number of cycles corresponding to the 0.5C / 80% capacity retention rate in Examples 1-25 were significantly improved; compared with Comparative Example 3, the number of cycles corresponding to the 0.5C / 80% capacity retention rate in Examples 1-25 was significantly improved. This demonstrates that forming a coating layer of block polymers (including both hydrophilic and hydrophobic polymer segments) on the surface of the electrolyte can effectively isolate moisture from the electrolyte, improve the electrolyte's air stability, and thus improve the battery's capacity retention rate. Although the room temperature ionic conductivity of Examples 1-25 decreased compared with Comparative Examples 1 and 2, it is still within an acceptable range.
[0216] As can be seen from Table 1, from Examples 1 to 11, the thickness of the coating layer is closely related to the degree of polymerization of the hydrophobic polymer segment PDMS and the degree of polymerization of the hydrophilic polymer segment PEG. The higher the degree of polymerization, the greater the thickness of the coating layer.
[0217] As shown in Table 1, compared with Examples 5 and 6, Examples 1-4 exhibit superior overall performance. This indicates that limiting the degree of polymerization of the hydrophobic polymer segment PDMS to the range of 700-2000 results in superior overall performance. Similarly, compared with Examples 10 and 11, Examples 1 and Examples 7-9 exhibit superior overall performance. This indicates that limiting the degree of polymerization of the hydrophilic polymer segment PEG to the range of 400-2000 results in superior overall performance. If the coating layer is too thick or the mass ratio of the hydrophobic segment is too high, the composite particles exhibit good hydrophobicity but increased insulation, leading to increased battery polarization and ultimately causing localized damage to the internal particle structure. Conversely, if the coating layer is too thin or the mass ratio of the hydrophilic segment is too high, the composite particles exhibit good ionic conductivity but insufficient air stability.
[0218] As can be seen from Table 1, compared with Example 1, the room temperature ionic conductivity and the number of cycles corresponding to 0.5C / 80% capacity retention in Examples 18-20 were further improved. It can be seen that the addition of lithium salt can improve the ionic conductivity of the block polymer and reduce battery polarization on the one hand, and coordinate with oxygen atoms on the polymer chain to reduce the activity of oxygen atoms and improve the contact stability between the polymer and the sulfide electrolyte on the other hand.
[0219] As can be seen from Table 1, compared with Example 1, the number of cycles corresponding to 0.5C / 80% capacity retention in Examples 21-23 was further improved. It can be seen that the addition of metal oxide can reduce the activity of oxygen atoms on polymer chain segments, further improve the cycle performance of the battery, and absorb a small amount of H2S generated by side reactions, thereby improving the overall safety of the battery.
[0220] As can be seen from Table 1, compared with Examples 1-23, Example 24 has the best overall performance. This shows that adding lithium salt and metal oxide to the coating layer can further improve the room temperature ionic conductivity and the number of turns corresponding to 0.5C / 80% capacity retention.
[0221] As can be seen from Table 1, compared with Example 25, Example 1 has better room temperature ionic conductivity and the number of cycles corresponding to 0.5C / 80% capacity retention. It can be seen that double bond end-capping design of block polymer can further improve its room temperature ionic conductivity and the number of cycles corresponding to 0.5C / 80% capacity retention.
[0222] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0223] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. An electrolyte composite material, characterized in that, include: Electrolytes; as well as A coating layer disposed on at least a portion of the surface of the electrolyte, the coating layer comprising a block polymer comprising hydrophilic polymer segments and hydrophobic polymer segments, the hydrophilic polymer segments being located on at least a portion of the surface of the electrolyte, and the hydrophobic polymer segments being located on at least a portion of the surface of the hydrophilic polymer segments away from the electrolyte.
2. The electrolyte composite material according to claim 1, characterized in that, The hydrophilic polymer segment includes at least one of polyether, polypolyamine, polypolyol, polypolyacid, polyamide, and polypolythiol.
3. The electrolyte composite material according to claim 2, characterized in that, The polyether includes at least one of polyethylene glycol, polypropylene oxide, and polybutene oxide; And / or, the polypolyamine includes at least one of polydopamine, polyacrylamide, ammonium polyphosphate, and deacetylated chitosan; And / or, the polypolyol includes at least one of polyvinyl alcohol, polyacryl alcohol, polybutenol, and polyhydroxycellulose; And / or, the polybasic acid includes at least one of polyacrylic acid, sodium polyacrylate, and polybutenoic acid; And / or, the polyamide includes at least one of polyacrylamide, propargylamide polymer, and sulfonated polyamide; And / or, the polythiols include at least one of mercapto polyethylene glycol thiols and polyvinyl thiols.
4. The electrolyte composite material according to claim 1, characterized in that, The degree of polymerization of the hydrophilic polymer segment is 200 to 2500.
5. The electrolyte composite material according to claim 3, characterized in that, The degree of polymerization of the polyethylene glycol is 400 to 2000.
6. The electrolyte composite material according to claim 1, characterized in that, The hydrophobic polymer segment includes at least one of polysiloxane, polyester, polyamine, saturated alkyl polymer and unsaturated hydrocarbon polymer.
7. The electrolyte composite material according to claim 6, characterized in that, The polysiloxane includes at least one of polydimethylsiloxane and its derivatives; And / or, the polyester comprises at least one of polymethyl methacrylate, polyacrylate, polycarbonate diol, and polyester fiber; And / or, the polyamine includes at least one of polyimide, polyethyleneimine, and chitin; And / or, the saturated alkyl polymer includes at least one of polyethylene, polyvinyl chloride, and polypropylene; And / or, the unsaturated hydrocarbon polymer includes at least one of polyacetylenes and their derivatives.
8. The electrolyte composite material according to claim 1, characterized in that, The degree of polymerization of the hydrophobic polymer segment is 500 to 3000.
9. The electrolyte composite material according to claim 7, characterized in that, The degree of polymerization of the polydimethylsiloxane is 700 to 2000.
10. The electrolyte composite material according to claim 1, characterized in that, The block polymer has a cross-linked network structure, and the structural formula of the block polymer is as follows: or Wherein, A is the hydrophilic polymer segment, Q is the hydrophobic polymer segment, CCR is the group formed by the double bond end-capping agent, n1 is a positive integer in the range of 100 to 2000, and n2 is a positive integer in the range of 100 to 2000.
11. The electrolyte composite material according to claim 10, characterized in that, The double bond end-capping agent includes an isocyanate end-capping agent, which includes at least one of isophorone diisocyanate and isocyanoethyl methacrylate.
12. The electrolyte composite material according to claims 1 to 11, characterized in that, The coating layer also includes metal oxides and / or lithium salts.
13. The electrolyte composite material according to claim 12, characterized in that, The mass ratio of the block polymer to the metal oxide is (4-16):1; And / or, the mass ratio of the hydrophilic polymer segment in the block polymer to the lithium salt is (2-8):
1.
14. The electrolyte composite material according to claim 12, characterized in that, The metal oxide includes at least one of Fe2O3, ZnO, TiO2, Bi2O3, and SnO2; And / or, the lithium salt includes at least one of LiPF6, LiBF4, LiClO4, LiAsF6, LiTFSI, LiFSI, LiBOB, LiDFOB, and LiTFOP.
15. The electrolyte composite material according to claims 1 to 11, characterized in that, The particle size D50 of the electrolyte is 0.5 μm to 5 μm; And / or, the thickness of the coating layer is 7nm to 30nm.
16. The electrolyte composite material according to claims 1 to 11, characterized in that, The electrolyte includes at least one of sulfide electrolytes, halide electrolytes, oxide electrolytes, and polymer electrolytes.
17. A method for preparing the electrolyte composite material according to any one of claims 1 to 16, characterized in that, include: Electrolytes, block polymers, and organic solvents are mixed to obtain a suspension; The suspension is subjected to solid-liquid separation and dried to obtain an electrolyte composite material.
18. The method according to claim 17, characterized in that, The mass ratio of the electrolyte to the block polymer is 1:(0.01 to 0.05).
19. The method according to claim 17, characterized in that, The electrolyte, the block polymer, the organic solvent, and the metal oxide and / or lithium salt are mixed to obtain a suspension.
20. The method according to any one of claims 17 to 19, characterized in that, The process includes, prior to solid-liquid separation of the suspension: The suspension, crosslinking agent, and initiator are mixed and heated.
21. The method according to claim 20, characterized in that, The mass ratio of the block polymer, the crosslinking agent, and the initiator is 1:(0.01~0.03):(0.001~0.007); And / or, the heating temperature is 45℃~60℃, and the heating time is 20min~40min.
22. The method according to claim 20, characterized in that, The crosslinking agent includes at least one of peroxide crosslinking agents, azo compound crosslinking agents, acrylate crosslinking agents, and epoxy resin crosslinking agents; And / or, the initiator includes at least one of azo initiators, peroxide initiators, and redox initiators.
23. A solid electrolyte membrane, characterized in that, The electrolyte composite material includes any one of claims 1 to 16 or any one of claims 17 to 22.
24. A solid-state battery, characterized in that, The electrolyte composite material includes any one of claims 1 to 16, the electrolyte composite material prepared by the method of any one of claims 17 to 22, or the solid electrolyte membrane of claim 23.
25. A battery pack, characterized in that, The electrolyte composite material includes any one of claims 1 to 16, the electrolyte composite material prepared by the method of any one of claims 17 to 22, the solid electrolyte membrane of claim 23, or the solid battery of claim 24.
26. An electrical appliance, characterized in that, This includes the solid-state battery of claim 24 or the battery pack of claim 25.